Influence of Date of Planting on the Growth and Yield of Locally Popular Traditional Aromatic Rice Varieties in Boro Season - Mannan, MA; Bhuiya, MSU; Akhand, MIM; Rana, MM (Journal of Science Foundation, 2013)
The experiment was conducted at the Bangladesh Rice Research Institute Farm, Gazipur, in boro season to determine the optimum planting date and to select the varieties having high yield potential. Traditional aromatic photoperiod sensitive fine rice varieties; Kalijira, Kataribhog, Chinigura and Badshabhog were transplanted from 10 December and continued up to 25 January, both in 2000 and 2001 years, at an interval of 15 days. Forty-day old seedlings were transplanted spaced at 20 cm x 20 cm. Results exhibited that plant tallness, number of tillers and dry matter increased with the advancement of planting dates. On the contrary, the number of panicles, grains panicle-1, panicle length, grain yield, straw yield and growth duration decreased with delaying of planting dates. The intermediate short stature plant type of Chinigura exhibited higher number of panicles (300-331 m-2) and comparatively heavier individual grain (12.25-12.31 g), consequently gave higher grain yield (2.79-3.53 t ha-1 ) planted with in December. However, in late planted situation in 10 January Kalijira exhibited higher number of panicles, grains panicle-1, resulted higher grain yield than the rest of the varieties. Thus, cultivation of traditional aromatic fine rice Chinigura and Kalijira have the potentiality to produced higher grain yield when planted in early December in Boro season. DOI: http://dx.doi.org/10.3329/jsf.v10i1.16275 J Sci Foundation, January-June 2012;10(1):20-28